Catalytic Asymmetric Allylic Alkylation of 3‐Arylated Piperidin‐2‐ones1. Issue 22 (17th June 2013) - Michon, Christophe; Béthegnies, Aurélien; Capet, Frédéric; Roussel, Pascal; de Filippis, Arnault; Gomez‐Pardo, Domingo; Cossy, Janine; Agbossou‐Niedercorn, Francine
Abstract: The preparation of optically active lactams from 3‐aryl‐2‐piperidinone is reported. The quaternary carbon stereocentres were formed using palladium‐catalysed asymmetric allylic alkylation reactions. The resulting enantioenriched compounds are useful intermediates for the synthesis and development of neurokinin antagonists. Abstract : The preparation of optically active lactams from 3‐aryl‐2‐piperidinones is reported. The quaternary carbon stereocentres were formed using palladium‐catalysed asymmetric allylic alkylation reactions. The resulting compounds are useful intermediates for the synthesis and development of neurokinin antagonists.